Water uptake dynamics under progressive drought stress in diverse accessions of the OryzaSNP panel of rice (Oryza sativa) - Gowda, Veeresh R. P.; Henry, Amelia; Vadez, Vincent; Shashidhar, H.E.; Serraj, Rachid (Commonwealth Scientific and Industrial Research Organisation, 2012)
In addition to characterising root architecture, evaluating root water uptake ability is important for understanding drought response. A series of three lysimeter studies were conducted using the OryzaSNP panel, which consists of 20 diverse rice (Oryza sativa L.) genotypes. Large genotypic differences in drought response were observed in this genotype panel in terms of plant growth and water uptake. Total water uptake and daily water uptake rates in the drought-stress treatment were correlated with root length density, especially at depths below 30 cm. Patterns of water uptake among genotypes remained consistent throughout the stress treatments: genotypes that initially extracted more water were the same genotypes that extracted more water at the end of the study. These results suggest that response to drought by deep root growth, rather than a conservative soil water pattern, seems to be important for lowland rice. Genotypes in the O. sativa type aus group showed some of the greatest water uptake and root growth values. Since the OryzaSNP panel has been genotyped in detail with SNP markers, we expect that these results will be useful for understanding the genetics of rice root growth and function for water uptake in response to drought.